Exploration of key genes and pathways in response to submergence stress in red clover (Trifolium pratense L.) by WGCNA - Panpan Shang; Lei Bi; Wenwen Li; Xiaoli Zhou; Yanlong Feng; Jiahai Wu; Bing Zeng (BMC Plant Biology)
Abstract Background Submergence stress is a prevalent abiotic stress affecting plant growth and development and can restrict plant cultivation in areas prone to flooding. Research on plant submergence stress tolerance has been essential in managing plant production under excessive rainfall. Red clover (Trifolium pratense L.), a high-quality legume forage, exhibits low tolerance to submergence, and long-term submergence can lead to root rot and death. Results This study assessed the microstructure, physiological indicators, and the key genes and metabolic pathways under submergence stress in the root system of red clover HL(Hong Long) and ZY(Zi You) varieties under submergence stress at 0 h, 8 h, 24 h, 3 d, and 5 d. Based on 7740 transcripts identified in the leaves at 0 h, 8 h, and 24 h submergence stress, Weighted Gene Co-expression Network Analysis (WGCNA) was performed on the differentially expressed genes (DEGs) at 8 h and 24 h. Functional annotation of the DEGs in the four key modules was obtained. Based on the results, the red clover root system exhibited epidermal cell rupture, enlargement and rupture of cortical thin-walled cells, thickening of the mid-column, and a significant increase in the number of air cavities and air cavity area of aeration tissue with the prolongation of submergence stress. The malondialdehyde content, relative conductivity, peroxidase, and superoxide dismutase initially increased and decreased as submergence stress duration increased. Four specific modules (cyan, purple, light cyan, and ivory) closely correlated with each stress were identified by WGCNA. The 14 obtained Hub genes were functionally annotated, among which six genes, including gene51878, gene11315, and gene11848, were involved in glyoxylate and dicarboxylic acid metabolism, carbon fixation in photosynthetic organisms, carbon metabolism, biosynthesis of pantothenic acid and CoA, flavonoid biosynthesis. Conclusion In this study, using WGCNA, the molecular response mechanisms of red clover to submergence stress was proposed, and the core genes and metabolic pathways in response to submergence stress were obtained, providing a valuable data resource at the physiological and molecular levels for subsequent studies of submergence stress tolerance in plants.